Questioning technology in Iran: Tracking the intersection of Islam, culture and philosophy / Hamidreza Mohammadi Doostdar - Hamidreza Mohammadi, Doostdar (2017)
This dissertation explores the relationship between technology and religion, a field that has been studied by philosophers such as Marx, Ellul and Noble. However, this study uniquely looks at the technology of death in two distinct but interrelated cases in Iran; first the slaughterhouse and seconds the automatic corpse washer. The slaughterhouse is a unique technological system that has a history of almost one hundred years in Iran. It has throughout the years, slightly changed in form, but its significance and nature has remained untouched. The slaughterhouse transgresses boundaries of human-animal relationships and deeply influences embedded religious values and practices of ritual slaughter. The automatic corpse washer, with a history of only two years in Iran, has targeted another critical aspect of religion and life that is ‘death’. This ethnographic research was inspired by three broad lines of inquiry: First, what was the basis of accepting or rejecting (or at least opposing) a certain type of technology? Second, what role does Islam as the accepted and governing religion in the country have in terms of its relationship with technology and how do Islamic scholars view certain types of technologies? And finally, how does the case of the automatic corpse washer and the slaughterhouse shed light on broader questions of philosophy, technology and Islam? Death and its ritual practices reflect and shape social and religious values. Modern ways of rationalizing death including issues of efficiency, calculability and hygiene practices have transformed how death is perceived in the Iranian Islamic society. With the help of Transcendent Philosophy, this research reveals hidden issues of fetishism and alienation and investigates how modern religious provisions and modern technologies challenge one another.